Strategic management of health care organizations - Ginter, Peter M.; Duncan, W. Jack (Walter Jack); Swayne, Linda E. (Hoboken, New Jersey : Wiley, 2018)
"A comprehensive guide to effective strategic management of health c are organizations. Strategic Management of Health Care Organizations pr ovides essential guidance for leading health care organizations through strategic management. This structured approach to strategic management examines the processes of strategic thinking, consensus building and d ocumentation of that thinking into a strategic plan, and creating and m aintaining strategic momentum all essential for coping with the rapidly evolving health care industry. Strategic Management of Health Care Org anizations fully explains how strategic managers must become strategic thinkers with the ability to evaluate a changing industry, analyze data , question assumptions, and develop new ideas. The book guides readers through the strategic planning process demonstrating how to incorporate strategic thinking and create and document a clear and coherent plan o f action. In addition, the all-important processes of creating and main taining the strategic momentum of the organization are fully described. Finally, the text demonstrates how strategic managers in carrying out the strategic plan, must evaluate its success, learn more about what wo rks, and incorporate new strategic thinking into operations and subsequ ent planning. This strategic management approach has become the de fact o standard for health care management as leadership and strategic manag ement are more critical than ever in coping with an industry in flux. T his book provides heath care management students as well as health care administrators with foundational guidance on strategic management conc epts and practices, tailored to the unique needs of the health care ind ustry. Included are a clear discussion of health services external anal ysis, organizational internal analysis, the development of directional strategies, strategy alternative identification and evaluation, and the development and management of implementation strategies providing an i nformative and insightful resource for anyone in the field. This new ei ghth edition has been fully updated to reflect new insights into strate gic thinking, new methods to conceptualize and document critical enviro nmental issues, practical steps for carrying out each of the strategic management processes, industry and management essentials for strategic thinkers , and new case studies for applying the strategic management p rocesses. More specifically, readers of this edition will be able to: C reate a process for developing a strategic plan for a health care organ ization. Map and analyze external issues, trends, and events in the gen eral environment, the health care system, and the service area. Conduct a comprehensive service area competitor analysis. Perform an internal analysis and determine the competitive advantages and competitive disad vantages. Develop directional strategies. Identify strategic alternativ es and make rational strategic decisions for a health care organization . Develop a comprehensive strategy for a health care organization. Crea te effective value-adding service delivery and support strategies. Tran slate service delivery and support plans into specific action plans. Th e health care industry$1 (Bs revolutionary change remains ongoing and organizational success depends on leadership. Strategic management has become the single clearest manifestation of effective leadership of he alth care organizations and the strategic management framework strength s are needed now more than ever. The Strategic Management of Health Car e Organizations provides comprehensive guidance and up-to-date practice s to help leaders keep their organizations on track"--s
Includes bibliographical references and index.
Keywords: Health facilities -- Administration; Strategic planning; Mission statements